2015
DOI: 10.1186/s12890-015-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of TB-PCR using EBUS-TBNA samples in patients with intrathoracic granulomatous lymphadenopathy

Abstract: BackgroundEndobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is widely used to perform mediastinal lymph node sampling. However, little information is available on polymerase chain reaction for Mycobacterium tuberculosis (TB-PCR) using EBUS-TBNA samples in patients with intrathoracic granulomatous lymphadenopathy (IGL).MethodsA retrospective study using a prospectively collected database was performed from January 2010 to December 2014 to evaluate the efficacy of the TB-PCR test using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The low sensitivity of culture as compared to that of Xpert MTB/RIF has also been attributed to the paucibacillary nature of extrapulmonary specimens with uneven distribution of bacilli and formation of clumps [26]. Such cases (Xpert MTB/RIF positive and TB culture negative) are likely to be true positives as corroborated by the high specificity of Xpert MTB/RIF [23, 25, 27]. In the current subgroup of Xpert MTB/RIF-positive and TB culture-negative patients, 22 of 25 patients showed granulomatous inflammation and three patients showed chronic inflammatory changes on histopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low sensitivity of culture as compared to that of Xpert MTB/RIF has also been attributed to the paucibacillary nature of extrapulmonary specimens with uneven distribution of bacilli and formation of clumps [26]. Such cases (Xpert MTB/RIF positive and TB culture negative) are likely to be true positives as corroborated by the high specificity of Xpert MTB/RIF [23, 25, 27]. In the current subgroup of Xpert MTB/RIF-positive and TB culture-negative patients, 22 of 25 patients showed granulomatous inflammation and three patients showed chronic inflammatory changes on histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Because the current study setting is endemic for TB, patients were treated for TB based on Xpert MTB/RIF results, histopathological findings and clinical symptoms, despite having a negative TB culture. Similar approaches have previously been used with successful treatment outcomes [27]. The possibility of cross-contamination is least likely because the Xpert MTB/RIF assay is a closed system and is processed in accredited laboratories [23].…”
Section: Discussionmentioning
confidence: 99%
“… 4 The indications for EBUS-TBNA have recently been expanded beyond malignant diseases to include benign diseases, such as sarcoidosis, tuberculous lymphadenitis, and fungal infections. 5 6 7 8 In addition, several studies of EBUS-TBNA in benign diseases mainly suspected tuberculosis and sarcoidosis showed a good diagnostic yield and low complication rates. 6 9 10 …”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] This was re-iterated in another Korean study on EBUS-TBNA in granulomatous lymphadenitis, wherein of the seven patients with NS cytology and negative smear results, Xpert MTB/RIF gave the diagnosis in four cases (57%). [ 8 ] Among the microbiological tests performed on TBNA samples, Xpert MTB/RIF appears to provide the highest yield. The percentage positivity for AFB in smears of TB with non-caseating granulomas is low, varying from 1.9% to 20%.…”
mentioning
confidence: 99%